2021
DOI: 10.1016/j.omtn.2021.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of miR-30c-5p promotes hepatocellular carcinoma progression by targeting RAB32

Abstract: Hepatocellular carcinoma (HCC) remains among the most lethal of human cancers, despite recent advances in modern medicine. miR-30c-5p is frequently dysregulated in different diseases. However, the effects and the underlying mechanism of miR-30c-5p in HCC are still elusive. Here, we show that miR-30c-5p is downregulated in HCC and significantly associated with survival and tumor size in patients with HCC. We demonstrate that aberrant miR-30c-5p markedly affects HCC cell proliferation and migration. Further expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the present study, it was demonstrated that TNF-α treatment significantly decreased the miR-30c-5p expression level in RAOECs. Previous studies have indicated that miR-30 family members, especially miR-30c-5p, act as protective factors in numerous solid tumors, such as non-small cell lung ( 39 ), pancreatic ( 40 ) and liver ( 41 ) tumors. Recently, miR-30c-5p has been reported to be closely associated with the development of cardiovascular diseases, including AS ( 19 ), diabetic nephropathy ( 42 ) and myocardial ischemia-reperfusion injury ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was demonstrated that TNF-α treatment significantly decreased the miR-30c-5p expression level in RAOECs. Previous studies have indicated that miR-30 family members, especially miR-30c-5p, act as protective factors in numerous solid tumors, such as non-small cell lung ( 39 ), pancreatic ( 40 ) and liver ( 41 ) tumors. Recently, miR-30c-5p has been reported to be closely associated with the development of cardiovascular diseases, including AS ( 19 ), diabetic nephropathy ( 42 ) and myocardial ischemia-reperfusion injury ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elucidating the main regulators and signaling pathways of malignant glioma in ltration, especially the mesenchymal transition and tumor aggression, is expected to improve GBM therapeutic outcomes. The role of Rab32 in tumors is poorly explored, with only few studies reporting that Rab32 promotes tumor progression in hepatocellular and ovarian cancers (20,34), but no study of Rab32 is performed on glioma. Here, we are the rst to address the mesenchymal transition and cell invasion roles of Rab32 in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Rab32 belongs to the Ras-like small GTPase superfamily, which regulate membrane dynamics, including membrane fusion/ ssion, exocytosis, and cytoskeletal tra cking (18,19). A recent study showed that Rab32 serves as an oncogene in hepatocellular carcinoma with the potential to promote the growth and invasion of tumor cells, while a higher level of Rab32 was strongly related to the advanced tumor stage and poor survival in patients with hepatocellular carcinoma (20). However, the role of Rab32 in GBM, as well as its underlying subcellular and molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Rab32 belongs to the Ras-like small GTPase superfamily, which regulate membrane dynamics, including membrane fusion/fission, exocytosis, and cytoskeletal trafficking [18,19]. A recent study showed that Rab32 serves as an oncogene in hepatocellular carcinoma with the potential to promote the growth and invasion of tumor cells, while a higher level of Rab32 was strongly related to the advanced tumor stage and poor survival in patients with hepatocellular carcinoma [20]. However, the role of Rab32 in GBM, as well as its underlying subcellular and molecular mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%